Al-Manhaj At-Taqabuli Fi Al-Dirasat Al-Lughawiyah Fi At-Turats Al-Arabi - Aliyya Laubaha, Siti; S. Inaku, Miskat (Assuthur: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to explain how the nature of the contrastive method (at-taqabuli), including how it is a contrastive analysis method, the benefits of contrastive analysis, and also the steps in conducting a contrastive analysis. In this study, the literature review method was used because this research was sourced from several literature articles and books related to research. The conclusion of this study is that contrastive analysis is a method of comparison between two languages or two dialects in a language. In terms of differences and similarities in terms of syntax, morphology and phonology.